THE PAPER CRAFTER'S BIBLE - Moad, Elizabeth; Proverbs, Jennifer; Adamson, Karl ([United Kingdom] : A DAVID & CHARLES BOOK, 2004)
Readers will discover a fresh way to learn new papercrafts with this comprehensive, illustrated volume. "Papercrafter's Bible is an indispensable guide to exploring a wide spectrum of papercraft techniques. It gives the beginner a foundation, the intermediate a refresher, and stimulates the advanced to extend his or her craft skills. Methods are demonstrated and then married modern papers, equipment and ideas to give readers confidence and inspiration to take their skills a stage further. Each technique is explained with step-by-step photographs and tips on specific materials and equipment. Handy hints and throughout suggest ways to combine techniques and materials for new and innovative looks and ways of working. Most of the techniques can be applied to card making, as well as gift boxes, gift bags, novelty wrap and simple stationery. "Papercrafter's Bible is sure to become the indispensable papercrafting sourcebook, revised time and time again.
Includes index
Keywords: Paper crafts; Handicraft; Paper work